Modelling of thermo-mechanical effects in a rock quarry wall induced by near-surface temperature fluctuations. (October 2020) - Marmoni, G.M.; Fiorucci, M.; Grechi, G.; Martino, S.
Abstract: Mechanical response of rock masses to the periodical fluctuation of surface temperatures is a relevant topic to be focused on for the comprehension of short- to long-term stability of rock slopes continuously stressed by slight yet periodical actions. To better understand how preparatory factors can lead rock masses toward failure, thermal and strain monitoring activities are ongoing in a selected quarry wall, where an experimental test-site was implemented on a jointed rock block. The role of pervasive joints in perturbing the heating-cooling process of the rock mass and their related effects was already output by direct and remote monitoring. For these purposes, FDM numerical modelling was focused on the comprehension and simulation of induced mechanical effects due to cyclical thermal forcings over a simplified 2D half-space. Therefore, the role of rock mass joints on both heat propagation and resulting thermo-mechanical effects was analysed, basing on monitoring data, field experiments and numerical modelling. Numerical results output the role of periodic daily, annual and compound thermal input in inducing irreversible deformation along joints under different rock mass jointing configuration, as a function of the intrinsic period of thermal input and joint attitude. Temperature distribution across joints was also analysed as a possible constraining effect for time and space distribution of yielding. A sensitivity analysis of heat propagation conditions was performed in order to infer the role of joint sets on induced thermo-mechanical strains at the rock block scale. A non-negligible influence on surficial as well as deeper portions of the rock mass was observed, highlighting how near-surface temperature fluctuations can drive the long-term evolution of rock block conditions towards failure. Highlights: Thermally induced strains in rock mass were numerically reproduced. Daily, annual and a composition of temperature variations were modelled. Thermo-mechanical sensitivity analysis was experimented. Jointing conditions markedly influence temperature fields. Temperature fields can control the distribution of rock failures.